What are the impacts of flow regime changes on fish productivity in temperate regions? A systematic map protocol - Trina Rytwinski; Jessica J. Taylor; Joseph R. Bennett; Karen E. Smokorowski; Steven J. Cooke (Environmental Evidence, 2017)
Abstract Background Ecosystem changes from altered flows can have multiple impacts on fish, including changes to physical habitat, habitat access, food supplies, behaviour, community composition, energy expenditure, and population dynamics. There is growing evidence of the potential negative consequences of altered flow regimes on fluvial ecosystems and the fisheries they support. As such, the scientific and policy communities have acknowledged the need for maintaining or restoring natural flow variability in order to sustain ecological health of fluvial ecosystems. However, for resource managers, making decisions on the potential effects of flow alterations on fish productivity has been problematic because there are still uncertainties regarding flow-fish productivity relationships. Therefore, to ensure the maintenance of healthy and productive aquatic ecosystems and the sustainability of riverine fisheries, a better understanding of the impacts of flow alteration on fish productivity is needed. Due to the wide scope of this review, and the diversity of fish productivity outcomes used to evaluate flow alteration impacts, the set of studies will be quite heterogeneous. Therefore, prior to undertaking a comprehensive and quantitative synthesis, we propose to begin with a systematic map to provide an overview of the available evidence on the impacts of flow regime changes on fish productivity. We will also use this systematic map to identify subtopics that are sufficiently covered by existing studies to allow full systematic reviewing. Methods This systematic map will compile evidence on the impacts of flow regime changes on fish productivity. All studies that evaluate the effects of flow regime change on direct outcomes of fish productivity, will be included in the review. We will use a broad definition of fish productivity to include any measurement related to: biomass, abundance, density, yield, diversity, growth, survival, individual performance, migration, reproduction, recruitment, or surrogate thereof. Relevant causes of a change in/modification to flow regime can include: (1) anthropogenic causes: dams, reservoirs (impoundments), hydroelectric facilities, locks, levees, water withdrawal (abstraction), water diversion, land-use changes, and road culverts; or (2) natural causes: climate change (possible indirect anthropogenic cause as well), floods, droughts, seasonal changes. Any freshwater or estuarine fish species or species groups in temperate regions will be considered. The review will include a wide range of sources including primary and grey literature and use public databases, search engines and specialist websites. A searchable database containing extracted meta-data from relevant included studies will be developed and provided as a supplementary file to the map report. The final narrative will describe the quantity and key characteristics of the available evidence, identify knowledge gaps for future research and identify subtopics that are sufficiently covered by existing studies to allow full systematic reviewing.